2021
DOI: 10.1186/s12935-021-01825-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC00470 in serum derived exosome: a critical regulator for proliferation and autophagy in glioma cells

Abstract: Background To explore the mechanism of LINC00470 in serum exosomes from glioma patients regulating the autophagy and proliferation of glioma cells. Methods Exosomes were extracted from glioma patients (GBM-exo). Expression of LINC00470 in exosomes was analyzed with the clinicopathological characteristics of glioma patients. Glioma mouse model was established. The effects of LINC00470, miR-580-3p and WEE1 on cell autophagy and proliferation, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…The results emphasized that silencing of CRNDE could impair the TMZ-induced autophagy in GBM cells through a reduction in the protein levels of LC3 II/I, Beclin 1, and Atg5, and an increase in those of p62. A recent study was reported that the lncRNA LINC00470 in GBM exosomes could inhibit autophagy and enhance the proliferation of glioma cells through binding to miR-580-3p to regulate WEE1 expression [ 39 ]. Similarly, silencing lncRNA DLEU1 could suppress TMZ-activated autophagy via regulating the expression of P62 and LC3, and promote sensitivity of glioma cells to TMZ by triggering apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results emphasized that silencing of CRNDE could impair the TMZ-induced autophagy in GBM cells through a reduction in the protein levels of LC3 II/I, Beclin 1, and Atg5, and an increase in those of p62. A recent study was reported that the lncRNA LINC00470 in GBM exosomes could inhibit autophagy and enhance the proliferation of glioma cells through binding to miR-580-3p to regulate WEE1 expression [ 39 ]. Similarly, silencing lncRNA DLEU1 could suppress TMZ-activated autophagy via regulating the expression of P62 and LC3, and promote sensitivity of glioma cells to TMZ by triggering apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that many exosomal lncRNAs could regulate tumor progression through “lncRNA–miRNA–mRNA” mode. As a dominant regulator of glioma cell autophagy, LINC00470 promoted the expression of ELFN2 through sponge of exosomal miR-101 to distract glioma cell autophagy ( 87 ). Activation of autophagy might be a clinical objective that contributes to therapeutic efficiency of immunogenic chemotherapy and/or radiation therapy.…”
Section: The Functional Role Of Exosomal Mirnas In Gliomamentioning
confidence: 99%
“…In addition, LINC00470 was overexpressed in GDEs and associated with disease severity and postoperative survival time of glioma patients [ 23 ]. LINC00470 in GDE could competitively bind to miR-580-3p in glioma cells to modify WEE1 expression and activate the PI3K/AKT/mTOR pathway, thus suppressing autophagy and strengthening the proliferation of glioma cells [ 23 ]. LncRNA ROR1-AS1 was upregulated in glioma tissues, and the high level of ROR1-AS1 predicted a poor prognosis [ 24 ].…”
Section: Gde Ncrnas In Remodeling Glioma Behaviorsmentioning
confidence: 99%